Antioxidant and Dietary Fibre Content of Noodles Produced From Wheat and Banana Peel Flour (IPS Journal of Nutrition and Food Science, 2023)
This study aimed to utilize flour from banana peel to develop functional noodles. Banana peel flour was substituted in wheat flour at 11, 13 and 15 %, was used to produce noodles. Composite noodles produced were evaluated for cooking characteristics, dietary fibre content, glycemic index, colour attribute and sensory evaluation. Result of cooking characteristics of the noodles indicated that the noodles containing banana peel flour had higher water uptake (10.25 – 11.25%) and cooking loss (6.28 – 7.59%) contents but an interestingly lower optimum cooking time (4.19 – 3.65 min) than their counterparts containing only wheat flour. The IDF value of the noodles varied from 8.26 - 12.18%. The highest value was observed in sample 13% and 15% banana peel flour supplemented with wheat flour while the lowest value was recorded in sample 100 % wheat flour. Increase in addition of banana peel flour led to an increase in antioxidant properties and dietary fibre content of the noodles. The glycemic index of the noodles varied from 58.74 - 65.28%. The highest value was observed in sample 100% wheat flour while the lowest value was recorded in sample 15% banana peel flour supplementation.  It was concluded that the use of flours from banana peels as composites of wheat had good potential for production of nutritionally and functionally superior noodles compared to the use of wheat alone. This study may be an economically viable approach towards promoting utilization of food wastes for production of value added products in developing countries.
Keywords: Noodles; Composite flour; Banana Peels; Heavy metals; anti-nutrients